Correlation Between Students’ Vocabulary Mastery and Reading Comprehension at Junior Islamic School - Pravitasari, Hikmah; Nurfadillah, Lena (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study investigated the correlation between students' vocabulary mastery and reading comprehension, conducted among eighth-grade students at an Islamic boarding school in Indonesia. The research aims to answer whether there is a correlation between students' vocabulary mastery and reading comprehension at the junior high school level. The population of this study was the eighth-grade students of junior Islamic school. The researcher selected students from classes A and B, with a total sample of 25 students chosen through a random sampling technique. The collected data was analyzed by using Pearson Product Moment correlation. The instruments used were vocabulary and reading tests. The results of this study showed that the calculated r-count was significantly higher than the tabulated r-table. Therefore, r-count (0.895) > r-table (0.396) indicated a positive correlation between vocabulary and reading. These findings suggested that students' vocabulary mastery had a significant influence on their reading comprehension abilities in eighth grade. It is emphasized that by building a strong vocabulary foundation, students are better equipped to comprehend the meaning and the core essence from the texts they read.